A dimension of well-being among talented students – An empirical study at the University of Debrecen - Mándy, Zsuzsanna; Filep, Roland; Dajnoki, Krisztina (Central European Journal of Educational Research, 2025)
Talent management in higher education remains a key issue, as university students are inherently talented when pursuing academic studies. Beyond this, many students engage in extracurricular activities, reflecting deeper personal motivations. This examines participants’ future career orientation in a university Talent Management Program by examining their life goals. While many students lack clear aims during their studies, we hypothesize that talented students show stronger self-acceptance, autonomy, and a commitment to continuous development and growth. The Ryff-18 questionnaire assessed students’ psychological well-being across six dimensions: self-acceptance, quality of relationships, autonomy, environmental mastery, purpose in life, and personal growth. The research is part of a longitudinal study, launched in the 2016/2017 academic year and repeated in 2023/2024, allowing for generational comparison between Generation Z and Millennials. All Talent Program students were invited to participate. In 2016/2017, 359 of 489 students responded (73.41%), and in 2023/2024, 201 of 671 (16.69%). Students rated “living day by day” highly in both years, and acquiring new experiences was low. Despite this, results indicate that participants are generally goal-oriented and prioritize long-term aims over novelty-seeking. These findings highlight consistent traits among talented students across generations.